The value of simulation-based training in the path to laparoscopic urological proficiency - Van Cleynenbreugel, Ben; Gözen, Ali Serdar; Tokas, Theodoros (Current opinion in urology, 2017)
Purpose of review Numerous factors have reduced the training opportunities of surgical residents in the operating room. There is also the question of patient's safety. This gives a need for increased training opportunities outside the operating room. We look if there is an added value in simulation-based training (SBT) in the acquisition of laparoscopic skills. Recent findings Incorporating SBT into the medical students curriculum reduces surgical complication rates in the operating room. Summary Reduction in opportunities to train surgical skills in the operating room, increased complexity of surgical procedures, and justified concerns for patients’ safety require training opportunities outside the operating room. Data proves that skills, acquired in the lab during SBT, are transferable to the operating room. Moreover, incorporating an evidence-based laparoscopic simulation curriculum shortens the clinical learning curve and reduces surgical adverse events.